SELECTING LIFT COLUMN DROP DEPTH AND DIAMETER TO PROVIDE LIQUID EXTRACTION CONDITIONS - Oripova, Shakhlo; Akramov, Bakhshillo; Adizov, Bobirzhon (Innovatsion texnologiyalar, 2024)
Today, due to the increase of hard-to-extract natural gas reserves in the world, as a result of the liquefaction of productive layers, the cases of the decrease in the flow rate of wells are increasing year by year. When using gas and gas condensate wells, liquid accumulation occurs at the bottom of the well. The cause of fluid accumulation in the bottom of the well is that the gas flow is not sufficient for complete removal. In this article, the main problem of using gas and gas condensate deposits using the PIPESIM software package of the Schlumberger company, the solution to determine the technological mode of operation of the well, which ensures stable operation without accumulation of formation and condensate liquid at the bottom of the well, was considered. A model of vertical gas well pipes of different diameters was built to determine the gas composition in well No. 118 in the Alan field and to calculate the operating modes of the well based on the results of gas-hydrodynamic research on steady-state flow regimes. To ensure the conditions of liquid removal, recommendations were made on the selection of the depth of the lift column and the diameter of the lift column. Based on the PIPESIM software, it has been scientifically proven that the lift column diameter is 60 mm or less.